2018
DOI: 10.1101/266858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary insights into Bean common mosaic necrosis virus and Cowpea aphid borne mosaic virus using global isolates and thirteen new near complete genomes from Kenya

Abstract: Plant viral diseases are one of the major limitations in legume production within sub Saharan Africa (SSA), as they account for up to 100 % in production losses within smallholder farms. In this study, field surveys were conducted in the western highlands of Kenya with viral symptomatic leaf samples collected. Subsequently, next-generation sequencing was carried out. The main aim was to gain insights into the selection pressure and evolutionary relationships of Bean common mosaic necrosis virus (BCMNV) and Cow… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…It is therefore likely that within the agro-ecosystems of western Kenya, there is heavy infestation of both aphids and whitefly vectors. Previous studies have reported aphid and whitefly-transmitted viruses in crops within the western region (Legg et al, 2006;Mangeni et al, 2014;Legg et al, 2014;Wainaina et al, 2018) and the Lake Victoria region (Tugume et al, 2010a;Adikini et al, 2015;Adikini et al, 2016). Moreover, farming practices within smallholder farms, which include partial harvesting of mature sweet potato, are thought to help maintain the virus within the agro-ecosystem.…”
Section: High Throughput Rna Sequencing Rna-seq On Sweet Potatomentioning
confidence: 97%
See 3 more Smart Citations
“…It is therefore likely that within the agro-ecosystems of western Kenya, there is heavy infestation of both aphids and whitefly vectors. Previous studies have reported aphid and whitefly-transmitted viruses in crops within the western region (Legg et al, 2006;Mangeni et al, 2014;Legg et al, 2014;Wainaina et al, 2018) and the Lake Victoria region (Tugume et al, 2010a;Adikini et al, 2015;Adikini et al, 2016). Moreover, farming practices within smallholder farms, which include partial harvesting of mature sweet potato, are thought to help maintain the virus within the agro-ecosystem.…”
Section: High Throughput Rna Sequencing Rna-seq On Sweet Potatomentioning
confidence: 97%
“…Within the Potyviridae, recombination is highly prevalent (Varsani et al, 2008;Elena et al, 2014 ;Ndunguru et al, 2015;Tugume et al, 2016;Wainaina et al, 2018). Moreover, co-infection of multiple viruses, in particular within sweet potato, can result in well-adapted viruses and has been adversely reported in other countries (Tugume et al, 2010a;Maina et al, 2017;Maina et al, 2018).…”
Section: Recombination In Sweet Potato Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…We then sampled symptomatic 77 common bean (Phaseolus vulgaris) leaves from the western highlands of Kenya as part of a larger 78 surveillance study on the heterogeneous cropping system in the western highlands of Kenya. RNA 79 extraction, cDNA library preparation and subsequent RNA sequencing on the Illumina Hiseq 2500 80 were carried out as previously described (Wainaina et al, 2018).…”
mentioning
confidence: 99%